2018
DOI: 10.1186/s12939-018-0861-6
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors of inequity in health services utilization among the elderly in China

Abstract: BackgroundWith the rise of the aging population, it is particularly important for health services to be used fairly and reasonably in the elderly. This study aimed to assess the present inequality and horizontal inequity for health service use among the elderly in China and to identify the main determinants associated with the disparity.MethodsThis cross-sectional study was based on the sample of the survey of the China Health and Retirement Longitudinal Study (CHARLS) for 2015. The elderly was defined as indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 25 publications
(29 reference statements)
5
68
0
Order By: Relevance
“…This can be explained that the use of inpatient services for middle-aged and elderly females in rural areas in less developed areas in China such as Jiangxi has been gradually enhanced since 2006. The medical security system is known to have an impact on the use of inpatient services [23,31,32]. Some studies have shown that patients enrolled in NRCM are more likely to seek health care services [2,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained that the use of inpatient services for middle-aged and elderly females in rural areas in less developed areas in China such as Jiangxi has been gradually enhanced since 2006. The medical security system is known to have an impact on the use of inpatient services [23,31,32]. Some studies have shown that patients enrolled in NRCM are more likely to seek health care services [2,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Research examining the disparity can be a consideration for the government to improve health facilities in rural areas. The government must be responsible for minimizing the disparity (Fu et al, 2018;Karuaihe and Wandschneider, 2018;Wong and Szeto, 2018;Li, Yao, and Yin, 2018;Song et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of healthcare utilization, rural beneficiaries have both higher probability and frequency of Introduction New Cooperative Medical Scheme (NCMS) has raised a lot of concerns, and disparity in healthcare utilization and expenditures is one of them [1] [2][3] [4]. These disparities indicate benefits of NCMS are concentrated toward economically affluent or scarce groups instead of distributing equally.…”
Section: Resultsmentioning
confidence: 99%